The quality of life and factors associated with it among disabled children and adolescents registered with selected community based rehabilitation (CBR), Department of Social Welfare, Kelantan - Ismail, Siti Fairuz (2016)
Determination of quality of life status and its associated factors among disabled children and adolescents is important because it can reflect the true feelings experienced by them. To determine the QoL status and factors associated with it, a cross-sectional study was conducted at the Community-Based Rehabilitation (CBR) centres in five districts in Kelantan. The study involved 419 disabled children and adolescents ages between 2 to 18 years old. The QoL status was measured using Paediatric Quality of Life Inventory (PedsQL) core scales and it showed that the QoL status among the disabled children and adolescents are increasing with their age. Study showed that the presence to CBR is one of the factors associated with the QoL status. Besides, gender and household income also has a relationship with the QoL status. The Multiple Logistic Regression (MLR) analysis was applied and four types of disability were found to be associated with the QoL status includes cerebral palsy (CP), Down syndrome, autism and medical problem. The probability of children and adolescents who have had CP, autism and medical problems to have a lower QoL status is increased by 13.1, 5.7 and 2.8 times. However, children and adolescents diagnosed as Down syndrome have a protective effect, by 0.4 times to have lower QoL status. Indirectly, this research will help professionals involved to improve the intervention programs and give special attention to the disabled who have disabilities such as CP, autism, Down syndrome and medical problem.